Conversational Disfluencies as a Predictor of Attention Problems in Preschool - Hart, Elizabeth (My University, 2008)
Attention Deficit Hyperactivity Disorder (ADHD) is frequently comorbid with language impairment. There is currently no detailed linguistic profile of children with ADHD. A previous study (Redmond, 2004) found that in conversation, children with ADHD produced more words per maze than typically developing controls, but did not determine the specific disfluency driving the correlation. The present study examined the conversational language, and measures of attention deficits, executive functioning and spatial intelligence of a non-clinical community sample of 46 preschool-aged children. The results replicated Redmond's finding and further indicated that attention deficits and executive dysfunctioning were associated with the production of more long repairs and restarts. The number of pauses was positively correlated with spatial abilities. Findings suggest that a preschooler who produces many long repairs and restarts should be monitored for possible attention deficits.
Title: Conversational Disfluencies as a Predictor of Attention Problems in Preschool, Author: Elizabeth Hart, Location: Thode